2018
DOI: 10.1111/jace.15408
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured mullite steam oxidation resistant coatings for silicon carbide deposited via atomic layer deposition

Abstract: Oxidation resistant, thin, pinhole‐free, crystalline mullite coatings were deposited on zirconia and silicon carbide particles using atomic layer deposition (ALD). The composition of the films was confirmed with inductively coupled plasma optical emission spectroscopy (ICP OES), and the conformality and elemental dispersion of the films were characterized with transmission electron microscopy (TEM) and energy dispersive X‐ray spectroscopy (EDS), respectively. The films are deposited on the particle surface wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…All the particle coating applications are derived either by the need to passivate an active surface or by functionalization of the surface for a particular purpose. Passivation is generally applied in the case of metallic powders to cease their spontaneous oxidation in air or to protect nonmetal powder particles from certain environmental attacks . On the other hand, surface-functionalized particles are finding numerous applications such as in pharmaceutics, biomedical engineering, UV-absorbance, catalysis, photocatalysis, thermite materials, electroluminescent materials, and sintering aid to ceramic particle processing .…”
Section: An Overview Of the Powder Ald Processmentioning
confidence: 99%
“…All the particle coating applications are derived either by the need to passivate an active surface or by functionalization of the surface for a particular purpose. Passivation is generally applied in the case of metallic powders to cease their spontaneous oxidation in air or to protect nonmetal powder particles from certain environmental attacks . On the other hand, surface-functionalized particles are finding numerous applications such as in pharmaceutics, biomedical engineering, UV-absorbance, catalysis, photocatalysis, thermite materials, electroluminescent materials, and sintering aid to ceramic particle processing .…”
Section: An Overview Of the Powder Ald Processmentioning
confidence: 99%
“…5b ). 26 Trimethyl aluminum (TMA), water, tris -dimethylaminosilane (TDMAS), and H 2 O 2 were used as the reactants, and the films were annealed at 1500 °C for 5 hours to be converted to the mullite phase. Reduced oxidation of silicon carbide by up to 62% could be obtained with a 10 nm ALD alumina film.…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, Hoskins et al ( 2018 ) have shown that an Al 2 O 3 or mullite (3Al 2 O 3 :2SiO 2 ) coating on SiC can reduce steam oxidation of the SiC at 1000 °C (20 h) by up to 62% for a 10-nm-thick ALD film on micron-sized SiC particles. These results are comparable to CVD films that are three orders of magnitude thicker and support the conclusion that the superior ECB properties using ALD films is the result of the films being free of pin-holes.…”
Section: Functionalized Particulate Materialsmentioning
confidence: 99%